2021
DOI: 10.1088/2053-1591/ac3e95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction stir processing on microstructures and mechanical properties of TIG cladding layer on AA7075

Abstract: AA7075 is a precipitation strengthened Al-Zn-Mg-Cu alloy which has been widely used. As a common way to repair AA7075 components, tungsten inert gas (TIG) cladding generates coarse grains and defects. In addition, the use of other types of filler wires could lead to insufficient rigidity and strength of the cladding layer. In the present work, friction stir processing (FSP) has been applied to the TIG cladding layer on AA7075 to study the effect of process parameters on microstructures and mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They observed that after FSP, there was substantial grain refinement with uniform distribution of intermetallic phases in the fusion region, resulting in a significant enhancement in weld corrosion resistance. Shi et al 24 explored the FSP to the TIG cladded layer on AA7075-T6-T6 alloys with filler ER5356 and examined its effect on microstructure, elemental distribution and mechanical properties. They concluded that following FSP, the macroscopic defects were reduced and fine grains were seen in the cladded zone, which increased the tensile and microhardness strengths.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that after FSP, there was substantial grain refinement with uniform distribution of intermetallic phases in the fusion region, resulting in a significant enhancement in weld corrosion resistance. Shi et al 24 explored the FSP to the TIG cladded layer on AA7075-T6-T6 alloys with filler ER5356 and examined its effect on microstructure, elemental distribution and mechanical properties. They concluded that following FSP, the macroscopic defects were reduced and fine grains were seen in the cladded zone, which increased the tensile and microhardness strengths.…”
Section: Introductionmentioning
confidence: 99%